2015
DOI: 10.3109/09638237.2014.998806
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of depressive symptoms in African American cancer patients

Abstract: Background Accurately assessing depression in African American cancer patients is difficult because of the similarities of physical symptoms observed in cancer and depression. Aim To identify universal and distinctive depressive symptoms in African American cancer patients. Methods Seventy-four cancer patients (34 depressed and 23 nondepressed African Americans, and 17 depressed Whites) were interviewed. Qualitative and quantitative analyses were conducted. Results Compared to nondepressed African Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Thirty-one articles were included in the final review [ 23 , 33 62 ], based on 28 independent studies from an original yield of 27,941 papers identified through searching, reference snowballing, related articles and expert recommendation. The full screening process is outlined in the PRISMA flowchart in the PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one articles were included in the final review [ 23 , 33 62 ], based on 28 independent studies from an original yield of 27,941 papers identified through searching, reference snowballing, related articles and expert recommendation. The full screening process is outlined in the PRISMA flowchart in the PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Outside of prostate cancer, African American men self‐report higher rates of depression than White men but have a lower likelihood of receiving a depression diagnosis or antidepressant treatment 11,12 . This raises the possibility of underrecognition and undertreatment of depression among African Americans 13‐15 . However, little is known about racial disparities in the incidence, treatment, and impact of depression on outcomes among men with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…37.9% of the Chinese population showing depressive symptoms and 4.1% of the population being diagnosed with clinical depression [ 13 ]. Evidence abounds as to the negative impact of depression on cardiovascular disease, memory performance, cognition and familial relationships [ 14 19 ]. However, less than 10% of depression patients in China were treated with antidepressant medications in 2016 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%